Pemikiran Filsafat Hukum tentang Keseimbangan Kebebasan Individu dan Keamanan Nasional dalam Hak Asasi Manusia - Rudijanto, Maria Natasha; Rasji, Rasji; Aurelia, Jessica (Peneliti.net, 2024)
Thinking in legal philosophy about the balance between individual freedom and national security in the context of human rights is an important debate in a democratic society. This study formulates the main problem with a focus on legal philosophy thinking on the concept of balance between individual freedom and national security and the policies that can be adopted by the government to maintain the balance. The article presents a review of the various perspectives and theories that underpin different approaches to this issue. While some views emphasize the importance of protecting individual rights as the foundation of democracy, others underline the need for strong measures to safeguard national security. The article also analyzes the various policies that can be pursued by the government to maintain such a balance, seeking common ground between the protection of human rights and the measures necessary to protect state security. It highlights the importance of legal philosophy thinking in guiding fair and balanced policymaking in the context of human rights